A survey of economics education at US community colleges. (9th September 2020) - Maier, Mark; Thornton, Tim
In order to increase the minimal knowledge about economics instruction at US community colleges we conducted a survey of instructors in May 2019. Although only 50 instructors responded to the invitation to participate, the survey offers preliminary insights about the economics curriculum and instructor characteristics. There appears to be widespread adoption of the OpenStax textbook Principles of Economics and minimal adoption of pluralist textbooks. Although most respondents believed they had significant or some scope to change the curriculum, they also registered some dissatisfaction with the current curriculum, noting the need for varied additions including behavioural economics, environmental economics, history of thought, and the study of income distribution. Respondents indicated a desire for greater respect by those working in four-year colleges and wanted more networking with the economics profession as well as financial support to attend conferences. Respondents identified increased use of online instruction and part-time instructors as worrisome trends, a majority believing both trends reduced student learning.